Geração de equações IDF dos municípios cearenses pelo método de desagregação por isozonas implementado em um programa computacional - Batista, Tatiane Lima (2018)
Understanding the characteristics of the intense rains of a certain locality is fundamental for the economic and safe design of hydraulic structures, flood prevention and water resource management. Two important parameters, intensity and duration of rainfall, may be statistically related to the frequency of occurrence. The resulting graphical representation is the so-called Curve or Equation IDF. An adequate IDF Equation is commonly needed for planning and design in the area of water resources. Many localities do not have an IDF Equation, which problem for designers. In order to meet this need for the state of the Ceará, this work has as main objective the development of the IDF Equations for the 184 municipalities of the state, based on a series of precipitation data annual maximums extracted from the rain gauge records. In the frequency analysis of the series were tested for the Gamma probability distributions with two and three parameters, Normal Log with two and three parameters and Gumbel. For the breakdown of daily rainfall in rainfall of shorter durations was applied to the methodology of isozones proposed by Torrico (1974). The methodology was applied through computational programming developed in computational language Java, in order to systematize the process of determining the Equations IDF. As a form of validation of the obtained results a the city of Fortaleza between the equation developed in this work and the equation determined by pluviograph data, generating excellent correlation indices.